(untitled) (European Journal of Mental Health, 2024)
Introduction: Good mental health literacy (MHL) enables an individual to access, understand, and use information in a way that promotes and maintains good mental health and facilitates early referral to mental health services. The literature reports that MHL levels among adolescents are gradually increasing, but still remain at low/moderate levels, and that this situation bears a negative impact on both individual and societal health. Aims: The Authors of this study aim to determine the level of MHL among university students engaged in the field of health, the factors that influence this level, and the differences between the various fields. Methods: The sample of this cross-sectional study consisted of 1,227 students enrolled in a university health department between 1 December 2022 and 20 January 2023. Data were collected online using a questionnaire designed by the researchers, and applying the MHL Scale (MHLS). We used descriptive statistics, one-sample t-test, one-way ANOVA test, multiple comparison tests (Tukey) and multiple linear regression in the statistical analysis. Results: The mean MHLS score of health faculty students was moderate (15.88, SD = 3.30). Female students, students aged >20 years and medicine, dentistry or nursing students had higher MHLS scores than others (p < .050). Conclusions: We observed that university students in the health sector did not have the desired or expected level of MHL. Improving MHL has the potential to facilitate early intervention, ensuring effective community mental health promotion and support; therefore, educational programs should be developed for this group.